Gene expression and organization of thylakoid protein complexes in the PSII‐less mutant of Synechocystis sp. PCC 6803. (6th June 2022) - Kılıç, Mehmet; Gollan, Peter J.; Lepistö, Anniina; Isojärvi, Janne; Sakurai, Isamu; Aro, Eva‐Mari; Mulo, Paula
Abstract: Photosystems I and II (PSI and PSII) are the integral components of the photosynthetic electron transport chain that utilize light to provide chemical energy for CO2 fixation. In this study, we investigated how the deficiency of PSII affects the gene expression, accumulation, and organization of thylakoid protein complexes as well as physiological characteristics of Synechocystis sp. PCC 6803 by combining biochemical, biophysical, and transcriptomic approaches. RNA‐seq analysis showed upregulated expression of genes encoding the PSII core proteins, and downregulation of genes associated with interaction between light‐harvesting phycobilisomes and PSI. Two‐dimensional separation of thylakoid protein complexes confirmed the lack of PSII complexes, yet unassembled PSII subunits were detected. The content of PsaB representing PSI was lower, while the content of cytochrome b6 f complexes was higher in the PSII‐less strain as compared with control (CS). Application of oxygraph measurements revealed higher rates of dark respiration and lower PSI activity in the mutant. The latter likely resulted from the detected decrease in the accumulation of PSI, PSI monomerization, increased proportion of energetically decoupled phycobilisomes in PSII‐less cultures, and low abundance of phycocyanin. Merging the functional consequences of PSII depletion with differential protein and transcript accumulation in the mutant, in comparison to CS, identified signal transduction from the photosynthetic apparatus to the genome level.